Northward shift of the southern westerlies during the Antarctic Cold Reversal. (1st November 2021) - Fletcher, Michael-Shawn; Pedro, Joel; Hall, Tegan; Mariani, Michela; Alexander, Joseph A.; Beck, Kristen; Blaauw, Maarten; Hodgson, Dominic A.; Heijnis, Henk; Gadd, Patricia S.; Lise-Pronovost, Agathe
Abstract: Inter-hemispheric asynchrony of climate change through the last deglaciation has been theoretically linked to latitudinal shifts in the southern westerlies via their influence over CO2 out-gassing from the Southern Ocean. Proxy-based reconstructions disagree on the behaviour of the westerlies through this interval. The last deglaciation was interrupted in the Southern Hemisphere by the Antarctic Cold Reversal (ACR; 14.7 to 13.0 ka BP (thousand years Before Present)), a millennial-scale cooling event that coincided with the Bølling–Allerød warm phase in the North Atlantic (BA; 14.7 to 12.7 ka BP). We present terrestrial proxy palaeoclimate data that demonstrate a migration of the westerlies during the last deglaciation. We support the hypothesis that wind-driven out-gassing of old CO2 from the Southern Ocean drove the deglacial rise in atmospheric CO2 . Graphical abstract: Image 1 Highlights: Empirical data demonstrate a northward shift of the southern westerlies during the Antarctic Cold Reversal (ACR). The northward shift of the southern westerlies during the ACR drove antiphase west-east environmental responses across Tasmania. Wetter conditions, lower fire activity and cold tolerant vegetation prevailed on western (windward) slopes during the ACR. Stronger westerly winds drive increased evaporation on the eastern (leeward) side of the Tasmanian mountains during the ACR. Consistent with models depicting global reorganisation of ocean and atmospheric circulation and heat transport during the ACR.